An Evaluation Of China’s Carbon Emission Reduction Policies On Urban Transport System - Jiaru, Hou; Xiangzhao, Feng (Journal of Sustainable Development Law and Policy, 2025)
Climate change has become one of the hottest issues in international law. As the world’s second-largest greenhouse gas emission sector, the transport sector, especially the urban traffic system, is facing much more pressure to reduce its aggregate emissions. This article begins with a theoretical examination of the system theory, takes the cobenefit concept as a methodological guide and discusses various urban traffic emission reduction policies such as travel demand management, vehicles policies, fuel policies, road policies and comprehensive management policies of the urban transport system. It argues that holistic policy reform is the most important means of promoting CO2 emission reduction effectively in urban traffic system. It is unrealistic to only implement one type of policy to achieve CO2 emission reduction targets in urban traffic system; a policy mix will arguably be of great significance to achieve and sustain emission reduction. Therefore, the promotion and perfection of policy system of CO2 emission reduction in urban traffic system and the intensification of policy innovation should be deemed a strategic choice to effectively realize CO2 emission reduction targets in urban traffic system, while promoting the sustainable development of the urban traffic system, the city and the economy.